ОБОСНОВАНИЕ ГРАНИЧНЫХ УСЛОВИЙ И ПОДСЧЕТНЫХ ПАРАМЕТРОВ ПОДЗЕМНЫХ ВОД НА ОСНОВЕ ГЕОИНФОРМАЦИОННО-МАТЕМАТИЧЕСКОГО МОДЕЛИРОВАНИЯ - Жумабаев, Р.П. (SCIENCE and SOCIETY, 2025)
This article examines the justification of boundary conditions and calculated parameters of groundwater movement using geoinformation and mathematical modeling. The work integrates field data, GIS tools and mathematical equations to determine the distribution and movement of groundwater in various hydrogeological conditions. The results obtained contribute to improving the accuracy of groundwater balance assessment and developing measures for their rational use.
Keywords: groundwater; boundary conditions; geographic information system; mathematical modeling; aquifer; flow calculation